The Influence of Job Training and Organizational Culture on Employee Job Satisfaction and Its Impact on Turnover at PT Len Industri (Persero) - Gustiawan, Devryansyah; Chandra, Rama; Rendy, Pras (Dinasti International Journal of Management Science, 2026)
This paper seeks to evaluate the effect of job training and organizational culture on job satisfaction and its effect on turnover intentions at PT Len Industri (Persero) after it changed its status to the Defense Industry Holding, Defend ID. This is due to the organizational restructuring and changes in human resources management that have resulted in changes in the organizational system, as evidenced by low scores in the Career and Development and Growth and Development factors, among others. This proposed study involves an associative quantitative approach with an explanatory design, where 162 valid questionnaires were collected through purposive sampling of employees in the directorate with the lowest performance score. The data were collected by a five-point Likert-scale questionnaire and analyzed by means of PLS-SEM using SmartPLS 4.0. Results indicate that both job training and organizational culture have positive and significant effects on job satisfaction, while the latter was the strongest predictor. Further, it is found that job satisfaction has a negative and significant effect on turnover intention and significantly mediates the relationships between job training and turnover intention as well as between organizational culture and turnover intention. These findings underlined the central role of job satisfaction as a psychological mechanism linking human capital development and organizational environment to employee retention and provided practical insights for strengthening training effectiveness and organizational culture in support of workforce stability in view of the Defend ID transformation.